PENGGUNAAN METODE FALLING HEAD DALAM MENENTUKAN DAYA SERAP AIR UNTUK MEREDUKSI GENANGAN DI KAMPUS FT-UMJ - Mohammad Imamuddin; Basit Al Hanif (Prosiding Semnastek, 2017)
ABSTRAKFaculty of Engineering University of Muhammadiyah Jakarta (FT-UMJ) as the oldest university in DKI Jakarta. In the period of 2002 to 2017, FT-UMJ did not escape from the puddle in the rain. Therefore, water absorption test in FT-UMJ page becomes very important in reducing the inundation. The ability of water to penetrate the soil as a medium is denoted as the permeability coefficient (k), the testing technique using the falling head method. From the results of the test that has been done by using the falling head method obtained coefficient value from the first test point of 5.5 m / day and the second test point 12.302 m / day. From this value, it is known that the soil type is silt clay which has low water drainage level.ABSTRAKFakultas Teknik Universitas Muhammadiyah Jakarta (FT-UMJ) sebagai perguruan tinggi tertua di DKI Jakarta. Dalam kurun waktu tahun 2002 hingga 2017, FT-UMJ tidak luput dari genangan pada saat hujan yang terjadi. Oleh karena itu uji daya resap air di halaman FT-UMJ menjadi sangat penting dalam mereduksi genangan yang terjadi. Kemampuan air untuk menembus tanah sebagai  media dilambangkan sebagai koefisien permeabilitas (k), Teknik pengujian menggunakan metode  falling head. Dari hasil uji yang telah dilakukan dengan menggunakan metode falling head didapat nilai koefisien dari titik percobaan pertama sebesar 5.5 m/hari dan titik percobaan kedua 12.302 m/hari. Dari nilai tersebut diketahui jenis tanah adalah lempung berlanau yang mempunyai tingkat pengaliran air kategori rendah. Kata kunci : Daya Serap Air, Infiltrasi, falling head. ABSTRAKFaculty of Engineering University of Muhammadiyah Jakarta (FT-UMJ) as the oldest university in DKI Jakarta. In the period of 2002 to 2017, FT-UMJ did not escape from the puddle in the rain. Therefore, water absorption test in FT-UMJ page becomes very important in reducing the inundation. The ability of water to penetrate the soil as a medium is denoted as the permeability coefficient (k), the testing technique using the falling head method. From the results of the test that has been done by using the falling head method obtained coefficient value from the first test point of 5.5 m / day and the second test point 12.302 m / day. From this value, it is known that the soil type is silt clay which has low water drainage level.